Microstrip Folded Dipole Antenna for 35 GHz MMW Communication - Guang Hua; Chen Yang; Ping Lu; Hou-Xing Zhou; Wei Hong (International Journal of Antennas and Propagation)
A microstrip asymmetric folded dipole antenna on chip is proposed in this paper. The construction of balun feed line is adopted to provide wideband. A new design procedure based on the odd-even mode method to calculate the input impedance of an asymmetric strip folded dipole antenna is presented. The folded dipole antenna has the advantage of small size, low profile, low cost, and so forth. The measured results show that a miniaturized antenna has the bandwidth of more than 14.2% (VSWR ≤ 2); gain of the antenna is 5.7 dB at 35 GHz.